Hispanic technocracy: from fascism to Catholic authoritarianism in Spain, Argentina, and Chile, 1945-1991 - Kressel, Daniel Gunnar (Cambridge Latin American studies, 2025)
Hispanic Technocracy explores the emergence, zenith, and demise of a distinctive post-fascist school of thought that materialized as state ideology during the Cold War in three military regimes: Francisco Franco's Spain (1939-1975), Juan Carlos Onganía's Argentina (1966-1973), and Augusto Pinochet's Chile (1973-1988). In this intellectual and cultural history, Daniel Gunnar Kressel examines how Francoist Spain replaced its fascist ideology with an early neoliberal economic model. With the Catholic society Opus Dei at its helm amid its 'economic miracle' of the 1960s, it fostered a modernity that was 'European in the means' and 'Hispanic in the ends.' Kressel illuminates how a transatlantic network of ideologues championed this model in Latin America as an authoritarian state model that was better suited to their modernization process. In turn, he illustrates how Argentine and Chilean ideologues adapted the Francoist ideological toolkit to their political circumstances, thereby transcending the original model.